The endangered freshwater pearl mussel Margaritifera margaritifera shows adaptation to a local salmonid host in Finland - Taskinen, Jouni; Salonen, Jouni K. (Wiley-Blackwell, 2022)
1. The freshwater pearl mussel Margaritifera margaritifera (FPM) is an endangered unionid which has a glochidium larva that attaches to the gills of Atlantic salmon Salmo salar or brown trout S. trutta, although some FPM populations have been shown to exclusively attach to only one of these species. The origin of host fish populations may be crucial for conservation actions for this mussel species, but the relative suitability of local (sympatric) and non- local (allopatric) salmonid populations as the hosts for FPM has been studied only rarely. We hypothesised that FPM glochidia would show adaptation to local salmonid strains and, there-fore, that they would be more successful (abundant, larger) attached to sympat-ric than to allopatric fish. 2. Here, we investigated the infection success (abundance and growth of encysted larvae in fish) of FPM in local versus non- local fish by caging different strains of brown trout and Atlantic salmon in rivers where FPM populations are present. 3. Higher abundances of glochidia in local fish were observed in three brown trout streams, and larger glochidia were found in sympatric hosts in one brown trout stream and in one salmon river. Furthermore, non- local allopatric fish were not better hosts than local fish in any of the FPM populations tested, neither in brown trout or salmon rivers and neither in abundance nor size of larvae. Therefore, the results supported the hypothesis that glochidia show local adap-tation by being more successful when attached to local fish strains. 4. Thus, the local, sympatric fish strain should be preferred in FPM conservation programmes that involve captive breeding of juvenile mussels and introduction of host fish, but the regional assessment of local host dependency of FPM also would be important outside the current study area. 5. The results also indicate the importance of restoration of original salmonid pop-ulations in FPM rivers to enable the natural, effective reproduction cycle of FPM in their original, sympatric hosts, and thus to ...